Digital marketing from the perspective of the producer/seller in the SMEs of textile and clothing industry - Dimitrijević Dragan; Dimitrijević Natalija; Adamović Živoslav (Tekstilna industrija, 2023)
The main component of generating high-quality, efficient and successful strategic marketing is, first of all, the definition of marketing strategies in accordance with business goals, that is, in accordance with the company's business strategy. Marketing strategy generation is the process of determining goals and choosing marketing strategies at the company level, aimed at specific markets, including the process of determining vision, mission and strategic goals, but also defining strategic positioning, i.e. detailed analysis of strengths, weaknesses, opportunities and threats of business and analysis of factors of the company's environment, as well as defining, choosing and implementing the strategy and auditing the results. As part of the marketing strategy, the marketing plan must be compatible with the business and marketing strategy, communication plans, Internet business plan and ICT strategy, which implies a detailed and precise definition of the basic elements of the marketing plan, as well as providing information about the markets in which business is conducted and current market conditions. movements, ways of measuring success, designing and planning marketing activities in certain time frames, as well as determining business strategy goals. The paper presents an explanation and analysis of the elements of effective digital marketing, which are necessary for the successful generation of marketing strategies and the effective implementation of marketing activity plans from the perspective of the manufacturer/seller, as well as an explanation and analysis of the elements of operational marketing, i.e. an explanation of the possible choices of digital marketing techniques, and recommendations for entrepreneurs SME textile and clothing industry.